Effect and mechanism of a novel Cordyceps militaris immunomodulatory protein on the differentiation of macrophages. (October 2021) - Fan, Hong-Bo; Zheng, Qian-Wang; Han, Qing; Zou, Yuan; Liu, Ying-Li; Guo, Li-Qiong; Lin, Jun-Fang
Abstract: Cordyceps militaris is a well-known fungus that contains multiple bioactive proteins providing various physiology benefits. However, limited studies on the immunomodulatory activity of C. militaris protein have been performed. This study intended to identify a C. militaris immunomodulatory protein (CMIMP) and determined its effect on macrophages. Using gene mining, a novel CMIMP was successfully identified. Sequence alignment and phylogenetic tree showed that CMIMP belonged to the fugal immunomodulatory protein (FIP) family. Detections on macrophages showed that CMIMP induced macrophages to differentiate into M1 phenotype, accompanied by increasing the secretion of proinflammation cytokines. Further experiments displayed that nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) pathways were activated, but NF-κB pathway was proved to be responsible for regulating CMIMP-triggered cell differentiation. In addition, instead of toll-like receptor 2 (TLR2), TLR4 was demonstrated to be the veritable receptor that mediated CMIMP-induced macrophage differentiation. In conclusion, CMIMP induced macrophages to M1 phenotype through the TLR4-NF-κB pathway and was a promising functional food ingredient or medicament. Graphical abstract: Image 1